2005
DOI: 10.4088/pcc.v07n0505
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report

Abstract: Background: Disulfiram, an agent used for the treatment of alcohol dependence, can exacerbate psychiatric syndromes (including psychosis, catatonia, delirium, depression, and mania) after extended use. However, delirium has yet to be reported following the short-term use of disulfiram in the setting of alcohol use.Objectives: We report a case with a neuropsychiatric presentation and discuss the prevention and the progression of delirium associated with an interaction of disulfiram and ethanol.Case Report: We r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…Furthermore, some mutations in ALDH isozymes have been described that lead to specific clinical phenotypes or diseases, and many of these diseases are characterized by neurologic abnormalities [ 5 ]. Disulfiram (Antabuse, TT), an ALDH inhibitor used to treat alcoholism, has been reported to cause significant neurologic toxicity in patients [ 43 , 44 ]. Thus, it is not surprising to detect such wide spread changes in the levels of multiple genes as revealed in our microarray analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some mutations in ALDH isozymes have been described that lead to specific clinical phenotypes or diseases, and many of these diseases are characterized by neurologic abnormalities [ 5 ]. Disulfiram (Antabuse, TT), an ALDH inhibitor used to treat alcoholism, has been reported to cause significant neurologic toxicity in patients [ 43 , 44 ]. Thus, it is not surprising to detect such wide spread changes in the levels of multiple genes as revealed in our microarray analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the previous studies suggest that delirium is associated with the disulfiram-ethanol reaction. 61,62 However, both the case reports in the present review reported onset of delirium like reaction without alcohol challenge.…”
Section: Discussionmentioning
confidence: 60%
“…Studies in the literature reported delirium induced by disulfiram-ethanol interaction and encephalopathy manifestations induced by disulfiram (24,25). Since our patient had not drunk alcohol while he was taking disulfiram, the possibility of disulfiram-alcohol interaction was eliminated.…”
Section: Discussionmentioning
confidence: 69%